Editorial - Melba Libia Cárdenas; María Claudia Nieto Cruz (Profile Issues in Teachers' Professional Development, 2017)
We have gathered thirteen articles in this edition; two of them come from Mexico, one from Chile, one from the United States, and nine of them are authored by Colombian scholars. . . . The articles present in our current issue depict the voices of academicians from Colombia, Mexico, Chile, and the United States. They reflect and act upon their realities and findings in specific contexts. Their very presence in our publication is a demonstration that we, as language teacher-researchers, have our own vision that merits the acknowledgment as active actors in the creation of local understanding that can be shared with and compared to the material and ideological experience of the West.